Combating Boko Haram insurgency: The role of Nigerian Military - Sekoni Ismael Obafemi; Abraham. E. Orhero (Department of Accounting Universitas PGRI Yogyakarta, 2025)
This study evaluated Nigeria’s counterinsurgency strategies against the Boko Haram insurgency. It employed a historical research design and used content analysis to interpret the data. The study involved a thorough review of existing literature and documents to extract relevant information. The data were analyzed using trend analysis methods. Findings showed that Nigeria’s military response to Boko Haram has been dynamic and multi-pronged, encompassing direct military engagements, institutional reforms, regional partnerships, and community-based strategies. Since the insurgency’s onset in 2009, the government has adopted a comprehensive approach, integrating military, legal, socio-economic, and diplomatic instruments to address the crisis, recognizing that lasting solutions require more than force alone. However, ongoing obstacles, such as inadequate logistics and outdated military hardware, have impeded progress. Intelligence lapses have also worsened the security situation, particularly in areas heavily affected by the insurgency. The study concluded that overcoming Boko Haram necessitates strong political commitment, operational transparency, increased regional cooperation, and a citizen-focused strategy that emphasizes security, justice, and inclusive development. Achieving sustainable peace will require a holistic, long-term effort. Among its recommendations, the study urged the Nigerian government to invest in modern military assets, such as surveillance systems, armored vehicles, and communication devices, and to establish efficient logistics and supply chains to support troops on the front lines better.